Is There a Right to Hope That God Exists? Evil and the Principle of Non-Parity - Mariña, Jacqueline (Religions, 2022)
In this paper, I respond to James Sterba’s recent book ‘Is a Good God Logically Possible?’ I show that Sterba concludes that God is not logically possible by ignoring three important issues: (a) the different functions of leeway indeterminism (and the political freedom presupposed by it) and autonomy (the two are very different things, even though both go under the name of freedom), (b) the differences in the conditions of agency in God and in creatures, (there is non-parity in how each must apply the single moral law), and (c) the non-parity between our knowledge and God’s. I provide a brief summary of Sterba’s arguments, and I develop the following points: 1. Sterba’s argument against a Free-Will Defense hinges on his conflation of political freedom and autonomy; 2. Sterba’s crucial premise for his argument against soul-making theodicies (namely, that the “Pauline Principle” should be applied univocally across God and creatures) is false; 3. Sterba’s arguments against skeptical theism depend on his assumption that our knowledge is comparable to that of God. In each case, Sterba either does not recognize non-parity between God and creatures or does not recognize the difference between the profane (e.g., political matters) and the sacred, (e.g., spiritual matters having to do with the inner nature of the soul’s development).